ELSI Priorities for Brain Imaging - Illes, Judy (2006)
As one of the most compelling technologies for imaging the brain, functional MRI (fMRI) produces measurements and persuasive pictures of research subjects making cognitive judgments and even reasoning through difficult moral decisions. Even after centuries of studying the link between brain and behavior, this capability presents a number of novel significant questions. For example, what are the implications of biologizing human experience? How might neuroimaging disrupt the mysteries of human nature, spirituality, and personal identity? Rather than waiting for an ethical agenda to emerge from some unpredictable combination of the concerns of ethicists and researchers, the attention of journalists, or after controversy is sparked by research that cannot be retracted, we queried key figures in bioethics and the humanities, neuroscience, media, industry, and patient advocacy in focus groups and interviews. We identified specific ethical, legal and social issues (ELSI) that highlight researcher obligations and the nonclinical impact of the technology at this new frontier.